Linking Asset Utilization and Leadership Commitment with Income through Optimizing Asset Utilization - Ali Baba Ismail; Syamsu Alam; Mursalim Nohong (Magister Management, Hasanuddin University, 2022)
This study aims to analyze the effect of asset utilization and leadership commitment on income through asset optimization in the case of Legal Entity Higher Education of Hasanuddin University. Data was collected using a questionnaire of five Likert scales and distributed to 44 respondents of the state civil apparatus. The collected data is then analyzed using the quantitative approach of path analysis. The results showed that asset utilization and leadership commitment have a positive and significant effect on the optimization of assets and the increase in income. The leadership commitment variable has a positive and significant effect on increasing income through asset optimization. The optimization of assets has a positive and significant effect on income.